Analysis of Curriculum Management in Early Childhood - Nadia Qurrota A’yun; Zahruddin; Hasyim Asy’ari (Tarbiyah Departement collaboration with AMCA, 2022)
This study aimed to determine the application and benefit of curriculum management in TK 'Aisyiyah Bustanul Athfal 42 Ciputat. The method used is descriptive qualitative research; primary and secondary data sources are used; Data collection techniques used interview, observation, and documentation techniques. The results of this study indicate that the curriculum at TK 'Aisyiyah Bustanul Athfal 42 Ciputat uses the 2013 curriculum specifically for TK 'Aisyiyah, which is integrated between Islamic education, Muhammadiyah, and Aisyiyahan education. There are four steps in implementing curriculum management in this school: 1) Planning, 2) Organizing and Coordinating, 3) Implementation and 4) Control/Evaluation. The benefits of implementing curriculum management in this school include: 1) with curriculum management, the use of existing resources in schools can be utilized to the fullest; 2) with planning for extracurricular and extracurricular activities programs that are adapted to the curriculum, kindergarten children get the opportunity to achieve maximum results in the learning process; 3 ) increase the level of effectiveness of teachers' teaching performance and kindergarten children's activities so that they are expected to be able to achieve the desired learning objectives; 4) increase efficiency and effectiveness in the teaching and learning process because it has been planned.